A personal connected health system for the Internet of Things based on the Constrained Application Protocol. (May 2015) - Santos, Danilo F.S.; Almeida, Hyggo O.; Perkusich, Angelo
Graphical abstract: Highlights: We present a system that enables Personal Health Devices to share information in home networks and with the Internet. The Constrained Application Protocol (CoAP) is used as underlying protocol. The CoAP communication model was adapted to the ISO/IEEE 11073 model in the proposed system. Results showed how the network overhead is around 50% lighter when compared to other protocols. Interoperability experiments demonstrated how the proposed solution can work with legacy systems. Abstract: The increasing costs of healthcare along with the increasing availability of new Personal Health Devices (PHDs) are the ingredients of the connected health vision. Also, a growing number of consumer electronic and mobile devices are becoming capable of taking the role of a health gateway, thus operating as a data collector for PHDs. In this context, we present a system that enables PHDs to share information in home networks and with the Internet based on a new Internet of Things protocol, namely the Constrained Application Protocol (CoAP). CoAP is used along with the IEEE 11073 family of standards, which is the main exchange data model for PHD communication. We discuss how the proposed system can be integrated to other connected health systems, such as a Universal Plug and Play healthcare system. We detail how the CoAP communication model was adapted to the IEEE 11073 model. We also present a real PHD prototype and its evaluation results. These results demonstrated the feasibility of the proposed solution, showing how its network overhead is around 50% lighter when compared to other protocols. Finally, we tested the proposed solution based on different scenarios, including a proof-of-concept integration with a service in the cloud, using different wireless physical interfaces.